Challenging the techno-politics of anonymity: the case of cryptomarket users. Issue 4 (3rd April 2017) - Bancroft, Angus; Scott Reid, Peter
ABSTRACT: Anonymity is treated as a problem of governance that can be subject to technical resolution. We use the example of the darknet to critically examine this approach. We explore the background assumptions that have been made about anonymity as a quality of social life. We conceive of anonymity as a way of engaging and maintaining social relationships in an anonymous mode. We draw on a study of darknet 'cryptomarket' users who mainly use the darknet to buy and sell illicit drugs, discuss drug quality and share information on safe and effective use. We identify the personal satisfaction that comes from interacting anonymously online, the challenges this represents for maintaining trusted interactions and how they are overcome, and the combination of technology and action involved in maintaining anonymity. We argue that attempts to promote de-anonymising norms and technology are based on an erroneous understanding of what anonymity is.